A review of the bandwidth and environmental discourses of future energy scenarios: Shades of green and gray. (January 2017) - Laugs, Gideon A.H.; Moll, Henri C.
Abstract: Energy scenarios are often used to investigate various possible energy futures and reduce the uncertainty that surrounds energy transition. However, scenario construction lacks consistent and adequate methodological standards, resulting in limited insight into the actual bandwidth covered by current energy scenarios and whether various perspectives on future energy development pathways are all adequately represented. Our research deployed a non-mathematical clustering approach to identify general trends in future energy scenarios and assess the role of Cornucopian and Malthusian oriented world views therein. We found that the futures communicated in quantified future energy scenarios overlap to a large extent and represent only a narrow bandwidth of moderate world views. We argue that the underrepresentation of extreme representations of world views and environmental discourses in energy scenarios skews the overall outlook on possible energy futures. This implies that scenario-informed policy design and decision-making risks bias towards the status-quo.